2016
DOI: 10.1007/s00249-016-1143-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intracellular ion channels on cancer development and progression

Abstract: Cancer research is nowadays focused on the identification of possible new targets in order to try to develop new drugs for curing untreatable tumors. Ion channels have emerged as “oncogenic” proteins, since they have an aberrant expression in cancers compared to normal tissues and contribute to several hallmarks of cancer, such as metabolic re-programming, limitless proliferative potential, apoptosis-resistance, stimulation of neo-angiogenesis as well as cell migration and invasiveness. In recent years, not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 333 publications
(324 reference statements)
0
33
0
Order By: Relevance
“…Interestingly, many of the K + channels found in the IMM (in addition to the PM and other membranes) are highly overexpressed in cancer cells/tissues. For example, the two‐pore leak channel K 2P 9.1(TASK‐3) is overexpressed five‐ to 100‐fold in 44% of breast tumours and is also highly expressed in lung, colon and ovarian cancers (Peruzzo et al ., ). Its overexpression promotes tumour formation and confers resistance to hypoxia in vitro , suggesting that its up‐regulation plays a pathologically important role in human breast cancer (Mu et al ., ).…”
Section: Inner Membrane Ion Channelsmentioning
confidence: 97%
See 2 more Smart Citations
“…Interestingly, many of the K + channels found in the IMM (in addition to the PM and other membranes) are highly overexpressed in cancer cells/tissues. For example, the two‐pore leak channel K 2P 9.1(TASK‐3) is overexpressed five‐ to 100‐fold in 44% of breast tumours and is also highly expressed in lung, colon and ovarian cancers (Peruzzo et al ., ). Its overexpression promotes tumour formation and confers resistance to hypoxia in vitro , suggesting that its up‐regulation plays a pathologically important role in human breast cancer (Mu et al ., ).…”
Section: Inner Membrane Ion Channelsmentioning
confidence: 97%
“…MCU is overexpressed in several type of cancer cells (e.g. Davis et al ., ; Peruzzo et al ., ; Bustos et al ., ) and has been implicated in cancer‐related processes, in particular in the control of migration and metastasis (Hall et al ., ; Tang et al ., ; Tosatto et al ., ; Szabo and Leanza, ).…”
Section: Inner Membrane Ion Channelsmentioning
confidence: 98%
See 1 more Smart Citation
“…Ion channels and transporters are some of the key modulators of cancer progression in hostile tumor microenvironment that includes hypoxia. It has been suggested that modulation of ion channels by the hypoxic environment may contribute to the aggressive phenotype observed in GBM cells residing in a hypoxic environment [22]. In hostile microenvironment such as hypoxia, BK Ca channels are modulated to aid cancer cell invasion and neovascularization.…”
Section: Metastatic Breast Cancer In Brain Microenvironmentmentioning
confidence: 99%
“…ClC‐1, ‐2, ‐Ka, and ‐Kb function as Cl − channels that localize at the plasma membrane, whereas ClC‐3 to ‐7 function as Cl − /H + transporters that distribute at intracellular vesicles such as endosomes/lysosomes and contribute to their acidification . Ion channels/transporters are expressed in several organelles such as mitochondria, endoplasmic reticulum, and endosomes, and intracellular ion channels play a role in the control of cancer development and progression . Intracellular ClC‐3 is highly expressed in metastatic cancer cells, accelerates cell migration, and contributes to the acquisition of resistance to chemotherapeutic drugs and anti‐HER2 therapies .…”
Section: Introductionmentioning
confidence: 99%